Endangered Species - Om Book international (Bharat Om Book International, 2018)
Emma, Eva and George eagerly go to the forest Reserve with their parents. But they are in for a rude shock when they see the beautiful deer eating the plastic bottles strewn about, the trees left as mere stumps, and litter everywhere. They learn from their parents why forests are so important and why it is necessary to preserve them and how! This brilliantly illustrated book is a must-read for kids to create awareness in their impressionable minds about how our planet can be saved from further damage.
Keywords: Sharing The Planet -- -Endangered Species